Fenofibrate in the management of AbdoMinal aortic anEurysm (FAME): Study protocol for a randomised controlled trial - Rowbotham, S.; Cavaye, D.; Jaeggi, R.; Jenkins, J.; Moran, C.; Moxon, J.; Pinchbeck, J.; Quigley, F.; Reid, Christopher; Golledge, J. (BioMed Central, 2017)
Background: Abdominal aortic aneurysm (AAA) is a slowly progressive destructive process of the main abdominal artery. Experimental studies indicate that fibrates exert beneficial effects on AAAs by mechanisms involving both serum lipid modification and favourable changes to the AAA wall. Methods/design: Fenofibrate in the management of AbdoMinal aortic anEurysm (FAME) is a multicentre, randomised, double-blind, placebo-controlled clinical trial to assess the effect of orally administered therapy with fenofibrate on key pathological markers of AAA in patients undergoing open AAA repair. A total of 42 participants scheduled for an elective open AAA repair will be randomly assigned to either 145 mg of fenofibrate per day or identical placebo for a minimum period of 2 weeks prior to surgery. Primary outcome measures will be macrophage number and osteopontin (OPN) concentration within the AAA wall as well as serum concentrations of OPN. Secondary outcome measures will include levels of matrix metalloproteinases and proinflammatory cytokines within the AAA wall, periaortic fat and intramural thrombus and circulating concentrations of AAA biomarkers. Discussion: At present, there is no recognised medical therapy to limit AAA progression. The FAME trial aims to assess the ability of fenofibrate to alter tissue markers of AAA pathology. Trial registration: Australian New Zealand Clinical Trials Registry, ACTRN12612001226897. Registered on 20 November 2012. © 2017 The Author(s).